2020
DOI: 10.46223/hcmcoujs.econ.en.10.2.967.2020
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Non-Performing Loans (NPLs) of banks: The case of Vietnam

Abstract: This study aims to identify factors affecting Non-Performing Loans (NPLs) of commercial banks in Vietnam. To address the research problem, data of commercial banks in Vietnam from 2008 to 2017 were collected. This study applied a fixed-effects model in comparison with a random-effects model on a panel data of 200 observations. Results from the firmly fixed-effects model indicated that NPLs were positively affected by its lag of the previous year, capital structure, and interest rate. Additionally, returns on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 4 publications
1
8
0
7
Order By: Relevance
“…There is research that has been conducted by Sinaga J, Muda I, and Silalahi in 2020 with the title the effect of bi rate, exchange rate, inflation, and third party fund (dpk) on credit distribution and its effect on nonperforming loan (npl) on xyz commercial segment bank, obtained the results of research on DPK and exchange rates In the commercial bank segment of XYZ, Inflation, the BI rate, and lending all have a significant impact on NPLs, whereas inflation, the BI rate, and lending have no impact on NPLs (Sinaga et al, 2020). Research by minh long in 2020 with the title factors affecting non-perfoming loans (NPLs) of banks: the case of viettnam obtained research results interest rates and capital structure have a positive effect on NPLs and ROA, inflation, credit growth has a negative effect on NPLs (Long et al, 2020).…”
Section: Loan To Deposit Ratiomentioning
confidence: 94%
“…There is research that has been conducted by Sinaga J, Muda I, and Silalahi in 2020 with the title the effect of bi rate, exchange rate, inflation, and third party fund (dpk) on credit distribution and its effect on nonperforming loan (npl) on xyz commercial segment bank, obtained the results of research on DPK and exchange rates In the commercial bank segment of XYZ, Inflation, the BI rate, and lending all have a significant impact on NPLs, whereas inflation, the BI rate, and lending have no impact on NPLs (Sinaga et al, 2020). Research by minh long in 2020 with the title factors affecting non-perfoming loans (NPLs) of banks: the case of viettnam obtained research results interest rates and capital structure have a positive effect on NPLs and ROA, inflation, credit growth has a negative effect on NPLs (Long et al, 2020).…”
Section: Loan To Deposit Ratiomentioning
confidence: 94%
“…There are various measurements of credit risk, and in this study, we used the NPL ratio (NPL_R) as developed by Abbas et al (2019); Kasinger et al (2021); Minh Long, Thi Yen, and Dinh Long (2020); Phung et al (2022); Pieter (2021) and Saleh and Abu Afifa (2020). As for the proxy for profitability, we used return on assets (ROA) (Abbas et al, 2019;Saleh & Abu Afifa, 2020) which demonstrated the use of ROA as a measurement of how effectively banks utilize their assets to generate returns.…”
Section: Hypothesis 2: Capital Has a Negative Relationship With Credi...mentioning
confidence: 99%
“…Penelitian Wairimu & Gitundu (2023) serta Gounder & Bajaj (2022) menyimpulkan bahwa suku bunga yang diukur dengan Real Interest Rate tidak berpengaruh terhadap NPL. Sejalan dengan hasil penelitian tersebut, Gultom & Sihombing (2023), Liviawati et al (2023) yang menggunakan variabel suku bunga bank sentral menyimpulkan bahwa tidak terdapat pengaruh suku bunga bank sentral terhadap NPL. Penelitian Poetry & Sanrego (2011), Oktaviani (2012) menyimpulkan hasil yang berbeda bahwa suku bunga yang di ukur dengan suku bunga bank sentral memiliki pengaruh negatif terhadap NPL.…”
Section: Pendahuluanunclassified
“…Kawasan ASEAN yang di dominasi oleh negara kategori berpenghasilan menengah dan kategori berpenghasilan rendah mencerminkan segmentasi bisnis perbankan lebih banyak ke pinjaman mikro dan ritel dibanding dengan pinjaman segmentasi korporasi (Tambunan, 2021). Penyaluran pinjaman kepada segmentasi pinjaman mikro dan ritel akan berdampak langsung pada perekonomian sehingga para debitur mampu meningkatkan penghasilan untuk membayar kewajiban pinjaman yang akan mengurangi risiko pinjaman atau nonperforming loan (NPL) akan semakin menurun, sejalan dengan penelitian Gabeshi (2017), Long et al (2020), Vithessonthi (2023). Maka, hipotesis penelitian ini adalah: H4: Pertumbuhan pinjaman berpengaruh negatif terhadap non-performing loan (NPL)…”
Section: Pengaruh Inflasi Terhadap Non-performing Loan (Npl)unclassified
See 1 more Smart Citation